Ocular manifestations of de-Morsiers syndrome - Arora, Priyanka; Arora, Kamaldeep; Utaal, Shubhneek K. D.; Chopra, Sumeet (International Journal of Contemporary Pediatrics, 2020)
A two-year old male child presented to the ophthalmology outpatient department (OPD) with parents complaining of child’s inability to make an eye contact. On examination, the patient had horizontal manifest nystagmus with no fixing and following. The pupillary reactions and the anterior segment examination were normal. Fundus examination in both eyes revealed small optic disc with 360 degree hyperpigmented ring in both the eyes (Figure 1 A and B). The macula was >2 disc diameter (DD) in distance from optic disc, suggestive of optic nerve hypoplasia. Magnetic resonance imaging (MRI) brain showed absent septum pellucidum (Figure 1 C and D). Serum growth hormone levels were significantly high. Based on the examination and investigations, diagnosis of de Morsier’s syndrome was made.